SHIP EMISSION ESTIMATION FOR IZMIR AND MERSIN INTERNATIONAL PORTS - TURKEY - Ekmekcioglu, Araks; Unlugencoglu, Kaan; Celebi, Ugur Bugra (YILDIZ TECHNICAL UNIV, 2019)
Approximately 90% of the world trade is done by sea trade. The world maritime trade fleet is also increasing every year. Since ships use fossil fuels, they contribute to global climate change. It is very important for the environment and human health to calculate emissions in the port areas where ships do cargo operations. In this study, emissions analysis of the two important ports of Turkey's is performed with using the bottom-up calculation method. In addition, hotelling periods of the vessels are monitored for both ports for one year period. As a result, total Nitrogen Oxide (NOx), Sulphur Dioxide (SO2), Carbon Dioxide (CO2), Volatile Organic Compounds (VOC), Particulate Matter (PM) and Carbon Monoxide (CO) emissions of Izmir Port are calculated as 900 tons/year, 589 tons/year, 45320.5 tons/year, 49.7 tons/year, 77.7 tons/year and 36.9 tons/year, respectively. Moreover, total NOx, SO2, CO2, VOC, PM and CO emissions of Mersin Port are calculated as 1998 tons/year, 1339 tons/year, 102330 tons/year, 114.5 tons/year, 178.5 tons/year and 82.5 tons/year, respectively. The amount of emissions of Mersin port, which has a higher number of movements, was higher than that of Izmir port.
Keywords: Shipping Emissions; Ports; Global Warming; Green Shipping; GASEOUS EMISSIONS; PARTICLE; REGION; IMPACT; SEA; Thermodynamics